Multipoint Observations of Energetic Particle Injections and Substorm Activity During a Conjunction Between Magnetospheric Multiscale (MMS) and Van Allen Probes. Issue 11 (27th November 2017) - Turner, D. L.; Fennell, J. F.; Blake, J. B.; Claudepierre, S. G.; Clemmons, J. H.; Jaynes, A. N.; Leonard, T.; Baker, D. N.; Cohen, I. J.; Gkioulidou, M.; Ukhorskiy, A. Y.; Mauk, B. H.; et al.
Abstract: This study examines multipoint observations during a conjunction between Magnetospheric Multiscale (MMS) and Van Allen Probes on 7 April 2016 in which a series of energetic particle injections occurred. With complementary data from Time History of Events and Macroscale Interactions during Substorms, Geotail, and Los Alamos National Laboratory spacecraft in geosynchronous orbit (16 spacecraft in total), we develop new insights on the nature of energetic particle injections associated with substorm activity. Despite this case involving only weak substorm activity (maximum AE <300 nT) during quiet geomagnetic conditions in steady, below‐average solar wind, a complex series of at least six different electron injections was observed throughout the system. Intriguingly, only one corresponding ion injection was clearly observed. All ion and electron injections were observed at <600 keV only. MMS reveals detailed substructure within the largest electron injection. A relationship between injected electrons with energy <60 keV and enhanced whistler mode chorus wave activity is also established from Van Allen Probes and MMS. Drift mapping using a simplified magnetic field model provides estimates of the dispersionless injection boundary locations as a function of universal time, magnetic local time, and L shell. The analysis reveals that at least five electron injections, which were localized in magnetic local time, preceded a larger injection of both electrons and ions across nearly the entire nightside of the magnetosphere near geosynchronous orbit. The larger ion and electron injection did not penetrate to L < 6.6, but several of the smaller electron injections penetrated to L < 6.6. Due to the discrepancy between the number, penetration depth, and complexity of electron versus ion injections, this event presents challenges to the current conceptual models of energetic particle injections. Key Points: Weak substorm activity during quiet geomagnetic conditions reveals the complex nature of energetic particle injections Fifteen spacecraft observe a series of electron injections but only one clear ion injection, injection boundaries estimated at different L There are two distinct injection types: localized in L and MLT with only electrons observed and broad range of L and MLT with ions and electrons